A comparison of the efficacy of pharmacotherapy and hypnotherapy in patients with primary dysmenorrhea - Tastan, Kenan; Nurcan Yoruk,; Ideal Beraa Yilmaz Kartal,; Nas, Mehmet Akif (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the efficacy of a single-dose 75mg diclofenac sodium tablet and single-session hypnosis for the treatment of primary dysmenorrhea. Method: The interventional, prospective, controlled study was conducted from May 23, 2022, to June 1, 2023, after approval from the ethics committee of Ataturk University Medical Faculty, Turkiye, and comprised primary dysmenorrhea female patients having visual analogue scale score >4. On the basis of Tastan Suggestibility Scale score <3 were placed in group A and were given 75mg diclofenac sodium tablets. Those with Tastan Suggestibility Scale score 3 or more were placed in group B and received hypnotherapy. Visual analogue scale was applied to both the groups again at 30 and 60 minutes post-intervention. Data was analysed using SPSS 22. Results: Of the 60 female patients, 30(50%) were in group A with mean age 27.3±6.7 years, and 30(50%) were in group B with mean age 27.3±6.6 years. The two groups were not significantly different in terms of age, education, marital status, working status, and previous treatment (p>0.05). VAS scores at baseline and 30 minutes post-intervention were not significantly different between the groups (p>0.05), but the decrease at 60 minutes post-intervention in group A was significantly greater than in group B (p<0.05). Conclusion: Pharmacotherapy and hypnotherapy were both effective in reducing pain in primary dysmenorrhea patients, but the effect of pharmacotherapy lasted longer than that of hypnotherapy. Key Words: Diclofenac sodium, Hypnotherapy, Primary dysmenorrhea.